Pengaruh Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Terhadap Motivasi Dan Hasil Belajar Siswa SMPN 2 Petir Pada Konsep Ekosistem - Hasrul Muftahid (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
This study is entitled "The Effect of the Team Assisted Individualization (TAI) Type of Cooperative Learning Model on the Motivation and Learning Outcomes of Lightning 2 Junior High School Students on Ecosystem Concepts". The purpose of this study was to determine the effect of the Team Assisted Individualization (TAI) type of cooperative learning model on the motivation and learning outcomes of SMPN 2 Lightning students on the ecosystem concept. The method used in this research is an experiment with a pre-test and post-test design, the instrument used is an objective test multiple choice form, and a questionnaire. The research was carried out at SMPN 2 Petir by taking samples of students in class VII D (experimental class) and VII E (control class). Sampling was carried out by random sampling technique. The results of the study obtained an average of 40.1 for the experimental class pre-test increased to 71.8 in the post-test value, while the average pre-test in the control class 37.4 increased to 58.4 in the post-test value. Judging from the calculation of the gain tcount (5.12)> ttable (2.38) it can be concluded that the cooperative learning model Team Assisted Individualization type can have a positive effect on motivation and student learning outcomes on the concept of ecosystem